Moderation By Organization-Based Self-Esteem of Role Condition-Employee Response Relationships - Pierce, Jon L.; Gardner, Donald G.; Dunham, Randall B.; Cummings, L. L. (Academy of Management Journal, 1993)
Behavioral plasticity theory is offered as an explanation for the moderating effects of self-esteem on role perception-employee response relationships. According to this theory, because individuals with low self-esteem are more reactive than their counterparts with high self-esteem, they are more susceptible to adverse role conditions, such as role conflict, ambiguity, and overload, and a poor work environment and poor supervisory support. Moderated hierarchical regression analyses revealed significant moderating effects for organization-based self-esteem on role condition-response relationships, thereby providing support for predictions based on behavioral plasticity theory.